2014
DOI: 10.7748/ncyp2014.05.26.4.32.e387
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and its importance for effective communication. Part 2

Abstract: This is the second of two articles exploring the concept of health literacy, an often hidden barrier to effective healthcare communication. Part 1 was published in April ( Lambert and Keogh 2014 ). This article explains how to detect low levels of health literacy among parents and children, and outlines the challenges to assessing health literacy levels, including the stigma and discrimination some people experience. Some basic healthcare communication strategies for supporting health literacy in practice are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…En relación a las barreras por parte de las mujeres, se ha establecido una relación entre la vergüenza y timidez con una baja literacidad de los pacientes, además de la posibilidad de experimentar discriminación (24,25). Por lo anterior es vital proveer un ambiente adecuado a las mujeres para que se sientan capaces de revelar abiertamente su necesidad de asistencia o confusión respecto a la información recibida (18).…”
Section: Tabla I Barreras En La Comunicación Percibidas Por Las Mujerunclassified
“…En relación a las barreras por parte de las mujeres, se ha establecido una relación entre la vergüenza y timidez con una baja literacidad de los pacientes, además de la posibilidad de experimentar discriminación (24,25). Por lo anterior es vital proveer un ambiente adecuado a las mujeres para que se sientan capaces de revelar abiertamente su necesidad de asistencia o confusión respecto a la información recibida (18).…”
Section: Tabla I Barreras En La Comunicación Percibidas Por Las Mujerunclassified
“…1,2 Low health literacy is associated with $106-$236 billion annually in increased hospitalizations. 3,4 Currently, there is no data on levels of health literacy in plastic surgery patients. A recent survey of ASPS members demonstrated that plastic surgeons overestimate the health literacy of their patients.…”
Section: Introductionmentioning
confidence: 98%
“…Health literacy is defined as an individual's ability to receive, acquire, understand, and use information; however, evolving conceptualizations of health literacy also include the caregiver's ability to communicate with other family members and the patient . Health literacy is multifaceted, including cognitive, social, and navigational skills such as language proficiency, reading, and numeracy skills, understanding risk and probability, and the communication skills needed to interact with a range of health care providers . Limited health literacy has been linked to poor disease management, nonadherence to treatment recommendations, increased hospitalizations, and patient or caregiver medication errors .…”
Section: Introductionmentioning
confidence: 99%